Morphofunctional changes in the immune system in colitis-associated colorectal cancer in tolerant and susceptible to hypoxia mice - Dzhuliia Dzhalilova; Maria Silina; Anna Kosyreva; Nikolai Fokichev; Olga Makarova (PeerJ)
Background One of the effective strategies for the treatment of tumor diseases, including colitis-associated colorectal cancer (CAC), is immunotherapy. During inflammation, NF-κB is activated, which is connected with the hypoxia-inducible factor—HIF, regulating the immune cells functioning and influences the CAC development. Organisms differ according to their hypoxia resistance and HIF expression. Therefore, the aim of the study was to characterize the thymus, spleen and mesenteric lymph nodes morphofunctional features, as well as changes in the subpopulation composition of peripheral blood cells and mesenteric lymph nodes in tolerant and susceptible to hypoxia C57Bl/6 mice in CAC. Methods Hypoxia tolerance was assessed by gasping time measurement in hypobaric decompression chamber. Based on the outcome, the mice were assigned to three groups characterized as ‘tolerant to hypoxia’, ‘normal’, and ‘susceptible to hypoxia’. A month after determining hypoxia resistance CAC was modeled by intraperitoneal azoxymethane (AOM) administration and three cycles of dextran sulfate sodium consumption. Mice were sacrificed on the 141st day after the AOM administration, a morphological, morphometric and immunohistochemical study of tumors, morphological and morphometric study of thymus and spleen, and subpopulation composition of peripheral blood cells and mesenteric lymph nodes assessment were carried out. Results Tumors in tolerant and susceptible to hypoxia mice were represented by glandular intraepithelial neoplasia and adenocarcinomas, the area of which was larger in susceptible mice. Immunohistochemical study revealed a more pronounced Ki-67+ staining in tumors of susceptible mice. In CAC, only in tolerant mice, expansion of the thymic cortex was observed relative to the control group, while in susceptible ones, no changes were detected. Only in susceptible to hypoxia mice, spleen germinal centers of lymphoid follicles enlargement were observed. Only in susceptible mice during CAC, in comparison to the control group, the relative and absolute number of B-lymphocytes and relative—cytotoxic T-lymphocytes in blood increased. The relative cytotoxic T-lymphocytes and NK cells number in peripheral blood during CAC was higher in susceptible to hypoxia mice compared to tolerant ones. In susceptible to hypoxia mice, more pronounced changes in the mesenteric lymph nodes subpopulation composition of cells were revealed—only in them the absolute and relative number of B-lymphocytes and NK cells, the absolute number of cytotoxic T-lymphocytes increased, and the relative number of macrophages decreased. Conclusions Morphofunctional differences in the thymus, spleen, mesenteric lymph nodes and blood immune cells reactions indicated the more pronounced immune response to the CAC development in susceptible to hypoxia mice, which should be taken into account in experimental studies.